Counselling Sexual-Violence Survivors: The Evolution of Female Counsellors’ Critical Political Consciousness and the Effects on Their Intimate Relationships - Garrity, Mary Kate (Canadian Journal of Counselling and Psychotherapy, 2010)
This social constructivist/constructionist research explores changes in female therapists’ intimate relationships after they began working with survivors of female sexual violence. Discourse analysis found that working with survivors shifted participants’ initially naive understanding of female sexual violence, as they developed a critical political consciousness of sexual violence in the process. Transformative learning theory is used to describe this process. As participants’ new consciousness developed, aspects of cognitive, emotional, and behavioural intimacy within their intimate relationships were affected. To better prepare therapists for working with survivors of female sexual violence, greater attention to counselling-training curricula is recommended.